DIALOG MUSIKAL: NEGOSIASI KONGAHYAN PADA RAGAM BENTUK MUSIK OLEH RAJJA RAVIAN ALAMSYAH - Nora Putri Sofyan; Habibullah, Reizki (Universitas Hamzanwadi, 2025)
This kind of research looks at cultural transformations through the lens of the traditional kobanga. Roughly termed as ‘crossover,’ the kobanga is a type of music where different genres are fused together. The focus is placed on the life of a Lukas Alamsyah Mohan, a young and upcoming musician from the Indonesian Art Institute in Surakarta. In the case of Betawi Culture, the Gambang Kromong art is turned to the stringed instrument Kongahayan. The konga is a traditional Indonesian instrument capable of undergoing changes in musical styles. Versatility is one of the strongest qualities of the konga. It is featured in a variety of modern genres like keroncong, and pop. Further, it incorporates along with and serves as the lead carrier for other instruments. This marks the integration of traditional Betawi into contemporary music Alamsyah's efforts are a testimony of the successful incorporation of various elements from different cultures into the music of Indonesia. This underscores the ability of the islam to act as a bridge between cultures and distinct ways of life. It encompasses the scope of hybrid and modern-day music, as well as the significance of the konga in advancing contemporary music in Indonesia.